Atividade antimicrobiana de plantas aromáticas que ocorrem no estado do Pará - Araujo, Isabella Santos (2011)
It was evaluated the antimicrobial activity of extracts of 37 herbs that occur in northeastern Pará, through the diffusion test in pit, 29 extracts, and the minimum inhibitory concentration MIC, 36 extracts, compared to 10 micro-organisms being Gram-positive bacteria, Gram-negative bacteria and yeasts. The micro-organisms more sensitive by the pit diffusion test and MIC were strains of Gram-positive bacteria. In comparison, the MIC methods proved more sensitive for determining the presence of antimicrobial activity of the extracts tested. Of the 29 gross extracts evaluated by pit diffusion method, 21 extracts showed activity against at least one micro-organism, with variation between part of the plant, type of micro-organisms and inhibited maceration of the solvent used to extract. Samples of the extracts also exhibited antimicrobial activity in the MIC determination, however, in different intensities, depending on the micro-organism and the extract studied. The detection of classes of secondary metabolites was performed by thin layer chromatography and the presence of terpenes, terpenoids, steroids, flavonoids and alkaloids occurred in five plant species studied. The in vitro results obtained here indicate that these species may act as antimicrobial agents against bacterial infections and yeast.